Robust image watermarking scheme by discrete wavelet transform - Abdullatif, Mohammad; Khalifa, Othman Omran; Olanrewaju, Rashidah Funke; Zeki, Akram M. (2014)
This paper proposes a robust digital image watermarking techniques by using discrete wavelet transform. The watermark is embedded in 2-level diagonal coefficient to achieve high performance in term of imperceptibility. The watermark is embedded by selecting a seed that generating pseudorandom noise sequence. Then the Watermark is extracted back by using the same pseudorandom noise sequence seed in the embedding. The experimental results show that the proposed algorithm provides good level of imperceptibility. Moreover, the watermarked image is robust against several attacks.